The causes of low vision and pattern of prescribing at UKM low vision clinic - Rokiah Omar,; Victor Feizal Knight,; Zainora Mohamed, (Penerbit UKM, 2008)
When medical and surgical intervention cannot alleviate all of the impairments resulting from diseases of the eye, visual rehabilitation can help reduce the disability and increase the quality of life. Data from 169 patients seen at the UKM Low Vision Clinic (UKM LVC) over the past 2 years were examined and analysed. The age ranged from 6 to 87 years of age. The main cause of ocular pathological categories was conduction (63.9%), media (24.9%) and congenital (11.2%) related problems. The main causes of low vision at UKM LVC were congenital cataract, retinitis pigmentosa, glaucoma, cataract and diabetic retinopathy. 84% of these patients received low vision devices to improve their near or/and distance vision. The most common optical devices dispensed at UKM LVC were near high addition spectacle, hand magnifiers and stand magnifiers. Medical,vision care and rehabilitation professionals working together can offer a comprehensive treatment plan for the visually impaired, offering these patients the very best services to increase their quality of life.